Design and Development of An Electronic Medical Record System For Maternal and Child Health and Dental Clinics at Camar Mandiri Primary Clinic, Jember - Mochammad Choirur Roziqin; Aylivia Fudya Ningrum; Bakhtiyar Hadi Prakoso; Indah Muflihatin; Gamasiano Alfiansyah; Muhammad Ifantara Putra (Universitas Duta Bangsa Surakarta, 2026)
Camar Mandiri Primary Clinic, particularly the Maternal and Child Health (MCH) and Dental outpatient units, has not yet implemented an Electronic Medical Record (EMR) system; consequently, patient registration and data recording are still performed manually. This condition is not in line with the Indonesian Ministry of Health Regulation No. 24 of 2022. This study aims to design and develop a web-based outpatient EMR system to improve service efficiency in the MCH and Dental clinics at Camar Mandiri Primary Clinic. This study employed a Research and Development (R&D) approach. Data were collected through observations and interviews involving two medical records staff, one dentist, one midwife, one pharmacist, and the clinic head. The system was developed using the waterfall method, which includes system flowcharts, context diagrams, Data Flow Diagrams (DFD), and Entity Relationship Diagrams (ERD). Data were collected through observation and interviews. The result is a web-based outpatient EMR system for the MCH and Dental clinics at Camar Mandiri Primary Clinic. Black-box testing results demonstrate that the system aligns with user needs, is user-friendly, and adequately supports clinical examination and reporting functions. Future development is recommended by adding more comprehensive and complex features, particularly modules related to pharmacy services and cashier management